Kinetics of processes in air plasma discharges at atmospheric pressure in the transverse flow of gas - Chernyak, V.Ya.; Tsymbaliuk, O.M.; Levko, D.S.; Martysh, E.V.; Iukhymenko, V.V.; Kolomiets, O.V.; Khomijak, V.O.; Chernysh, D.O.; Fentisova, O.I. (Вопросы атомной науки и техники, 2019)
The paper is devoted to the consideration of some features of the kinetics of the formation of nitrogen oxides and the population of the vibrational levels of the basic electronic states of nitrogen and oxygen molecules in the plasma of dry and humid air of gas discharges in the transverse gas flows to the current channel of the discharge at atmospheric pressure.